PENGARUH PENDAPATAN DAERAH TERHADAP BELANJA MODAL PADA KABUPATEN/KOTA JAWA TIMUR - Permatasari, Isti; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to test whether income of region that consist of Local Own Source Revenues(PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Profit Sharing Fund (DBH)have an influence to the Capital Expenditure in the districts / cities in East Java province in 2010-2014 periods.The samples are 38 districts / cities in East Java province. The data is in the form of secondary data which hasbeen obtained from the realization of Local Government Budget (APBD) report of districts / cities in East Javaprovince and the observation is in 2010-2014 periods that have been obtained from the Statistics Indonesia(BPS) of East Java Province. The data analysis instrument that has been employed in this research is MultipleLinear Regressions Analysis. Based on the result of the test, it shows that 1) Local Own Source Revenues haspositive influence to the Capital Expenditure; 2) General Allocation Fund has positive influence to the CapitalExpenditure; 3) Special Allocation Fund has positive influence to the Capital Expenditure. 4) Profit SharingFunds has positive influence to the Capital Expenditure. The result of this research has positive effect, itindicates when PAD, DAU, DAK, and DBH variables are getting high, and so the allocation of CapitalExpenditure is getting high as well.Keywords: Local Own Source Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund(DAK), Profit Sharing Fund (DBH), Capital Expenditure